"But I Gathered My Courage": HIV Self-Testing as a Pathway of Empowerment Among Ugandan Female Sex Workers. (February 2021) - Wachinger, Jonas; Kibuuka Musoke, Daniel; Oldenburg, Catherine E.; Bärnighausen, Till; Ortblad, Katrina F.; McMahon, Shannon A.
HIV self-testing (HIVST) increases HIV testing in diverse populations, but little is known about the experiences of individuals who self-test. We used a five-step framework approach to analyze 62 qualitative interviews with 33 female sex workers (FSWs) participating in an HIVST trial in urban Uganda. Notions of empowerment emerged from the data, and findings were interpreted based on Kabeer's empowerment framework of resources, agency, and achievements. We found that access to HIVST bolstered empowerment because it increased participant's time and money (resources), control of testing circumstances and status disclosure (agency), and sense of competency (achievements). In addition, we found that knowledge of HIV status empowered participants to better control HIV-related behaviors (agency) and recognize a new sense of self (achievements). This suggests that the availability of HIVST can facilitate feelings of empowerment, meriting a higher awareness for benefits outside of linkage to HIV treatment and prevention services.